Pemberdayaan Relawan Dalam Upaya Penanggulangan Kekerasan Terhadap Anak - Mawarti, Triyani; Djannah, Siti Nur; Sunarsih, Tri (Universitas Respati Yogyakarta, 2019)
Child abuse in Indonesia is increasing every year. In 2011 there were 2178 cases of violence, in 2012 there were 3512 cases, in 2013 there were 4311 cases, in 2014 there were 5066 cases (KPAI, 2015). Of these cases, there were 5 of the highest cases from 2011 to April 2015, namely (1) children dealing with the law recorded 6006 cases, (2) cases of care 3160, (3) education cases 1764, (4) health cases and drugs 1366 and ( 5) cases of pornography and cybercrime 1032. Where also need to be known that there are 3 child locus of violence, namely: family environment, school environment and community environment. Many parents consider child abuse to be a natural thing. These acts of violence can have both physical and psychological impacts. Both parents and the public do not understand the existence of hazards that threaten child safety and awareness of the need for child protection from threats of violence and sexual crimes are still low. This condition is clearly very alarming and requires precautionary measures for subsequent sacrifices involving various parties. The government does have to take the main part of the prevention effort, both through impartial policy formulation and applicable operational programs. In addition, various social organizations must also be seriously involved in their efforts to anticipate more violence and sexual crimes against children.Â The Community Partnership Program (PKM) is packaged by designing a social movement together by forming a volunteer group to protect children from the Panggungharjo Village community as an effort to prevent and deal with cases of violence against children. The method used in this activity includes TOT or child protection volunteer training in Panggungharjo Village can be described as a pyramid, in line with the pyramid of psychosocial recovery services.Keywords: Empowerment, Volunteer, Countermeasures, Child ViolenceÂ